2018
DOI: 10.1039/c8ra03081b
|View full text |Cite|
|
Sign up to set email alerts
|

Up-regulation of exosomal miR-125a in pneumoconiosis inhibits lung cancer development by suppressing expressions of EZH2 and hnRNPK

Abstract: Exosomal miR-125a may act as a bridge between pneumoconiosis and lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…The dominant role of autophagy in the proliferation, migration, and invasion of lung cancer cells has been well-established throughout previous studies (35). However, the mechanism underlying the initiation of autophagy is still unclear.…”
Section: Introductionmentioning
confidence: 77%
“…The dominant role of autophagy in the proliferation, migration, and invasion of lung cancer cells has been well-established throughout previous studies (35). However, the mechanism underlying the initiation of autophagy is still unclear.…”
Section: Introductionmentioning
confidence: 77%
“…Both of these factors simultaneously target WASL and VASP inducing inflammatory responses in lung tissue [ 8 ]. Moreover, let-7a was shown to be differentially expressed in different subtypes of non-small cell lung cancer [ 9 11 ]. Therefore, let-7 families may be useful as specific biomarkers for distinguishing different subtypes of lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…6 Currently, multiple miRNAs are known to participate in regulating the proliferation, differentiation, metabolism, and apoptosis of tumor cells. [14][15][16] The study has revealed that miR-125b controls proliferation and apoptosis by downregulating P53 and the genes involved in the P53 pathway including BAK1 and PUMA, which provides for the first time a potential mechanism for the development of secondary hematologic malignancies in patients treated with IMiD compounds. 9,10 Studies have shown that miR-125b acts as a tumor-suppressor gene in chronic lymphocytic leukemia (CLL) and MM, 11,12 whereas miR-125a is a newly discovered member of miR-125, whose precursor can produce two kinds of mature miR-125a-3p and miR-125a-5p, 13 which have also been reported to be tumorsuppressor genes in various malignant tumors, such as prostate tumor, lung tumor, and ovarian tumor.…”
mentioning
confidence: 99%
“…9,10 Studies have shown that miR-125b acts as a tumor-suppressor gene in chronic lymphocytic leukemia (CLL) and MM, 11,12 whereas miR-125a is a newly discovered member of miR-125, whose precursor can produce two kinds of mature miR-125a-3p and miR-125a-5p, 13 which have also been reported to be tumorsuppressor genes in various malignant tumors, such as prostate tumor, lung tumor, and ovarian tumor. [14][15][16] The study has revealed that miR-125b controls proliferation and apoptosis by downregulating P53 and the genes involved in the P53 pathway including BAK1 and PUMA, which provides for the first time a potential mechanism for the development of secondary hematologic malignancies in patients treated with IMiD compounds. 17 However, there are relatively few studies on the effect of miR-125a on hematological diseases.…”
mentioning
confidence: 99%